2017
DOI: 10.1080/20020317.2017.1297017
|View full text |Cite
|
Sign up to set email alerts
|

The Norwegian Early Childhood Education and Care institution as a learning arena: autonomy and positioning of the pedagogic recontextualising field with the increase in state control of ECEC content

Abstract: When the responsibility for ECEC institutions was placed under Ministry of Education and Research in 2006, the ECEC institution as a learning area was brought in to the foreground in early education and care policy. Norwegian ECEC institutions have been subject to a greater degree of state control, and we can ask if the state is trying to undermine the profession's autonomy through a strong degree of control over the content in education. This article is based on interviews with eight preschool teachers with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Appendix A shows that in 82 of the 106 publications (77.4%) that do not have assistants as informants, the topics under investigation might be equally relevant for assistants to offer their perspectives. Topics such as what is going on in the kindergarten, play, learning, interactions, gender and migrant children (see, for example, Bae, 2012;Kalkman, 2017;Kasin & Slåtten, 2015;Nygård, 2017) might generate a more diverse set of views if assistants were also included. Various occupationally specific challenges and dilemmas might be illuminated.…”
Section: Main Findingsmentioning
confidence: 99%
“…Appendix A shows that in 82 of the 106 publications (77.4%) that do not have assistants as informants, the topics under investigation might be equally relevant for assistants to offer their perspectives. Topics such as what is going on in the kindergarten, play, learning, interactions, gender and migrant children (see, for example, Bae, 2012;Kalkman, 2017;Kasin & Slåtten, 2015;Nygård, 2017) might generate a more diverse set of views if assistants were also included. Various occupationally specific challenges and dilemmas might be illuminated.…”
Section: Main Findingsmentioning
confidence: 99%
“…Number of studies have shown that quality of preschool plays a major function in moderating the effect of it attendance on child outcomes (Anders et al, 2012(Anders et al, , 2013Belsky et al, 2007;Burshinal et al, 2009;Vandell et al, 2010). In Sweden as well as in Norway, it is an increased control from the state regarding the quality of preschool (National Agency for Education, 2016a; Nygård, 2017;Taguma et al, 2013). Quality in relation to children's learning is in focus (Nygård, 2015).…”
Section: Systematic Quality Workmentioning
confidence: 99%
“…The introduction of the Educational Act (SFS, 2010:800) for preschools means that there are more governance documents from the state which influence the preschool practice especially the systematic quality work as well as teaching (cf. Nygård, 2017). This means a clearer governing concerning the content as well as more demands on the competence of the staff (Nygård, 2017).…”
Section: Governance and Management In Preschoolmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, they illuminate how education policy in the Nordic countries makes use of governing tools that enter directly into teaching and learning situations and as such have an impact on both the practices of education and the knowledgebase that these practices are influenced by. The contributions also emphasise how tensions emerge when new policy expectations of state controlled content learning meet the long-term experiences of teachers, for example in early childhood education (Nygård, 2017) or in the use of projects to promote integration of pupils with immigrant backgrounds in order to improve their school achievements (Gustafsson, 2017).…”
Section: Editorialmentioning
confidence: 99%